Computer-Based Rehabilitation for Developing Speech and Language in Hearing-Impaired Children: A Systematic Review. (June 2015) - Simpson, Andrea; El-Refaie, Amr; Stephenson, Caitlin; Chen, Yi-Ping Phoebe; Deng, Dennis; Erickson, Shane; Tay, David; Morris, Meg E.; Doube, Wendy; Caelli, Terry
Abstract : The purpose of this systematic review was to examine whether online or computer-based technologies were effective in assisting the development of speech and language skills in children with hearing loss. Relevant studies of children with hearing loss were analysed with reference to (1) therapy outcomes, (2) factors affecting outcomes, and (3) publication and methodological quality. The study quality was assessed using the 11-point PEDro scale. The review identified ten studies of relevance to the question of interest. All studies had relatively low PEDro quality scores with only four studies scoring in the mid-range on the scale. For these four studies, computer-based training appeared favourable at the group level. However, the small number of studies found significantly limits the generalizations and indicates the usage of these technologies in this population as an area requiring further rigorous research.